A styrene-conjugated diene-styrene triblock copolymer and its coupled complex elastomer, and a preparation method and application thereof

CN117186326BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210616375.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-01
Publication Date
2026-10-30
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

[0008]针对现有的三嵌段结构,以及偶合型的SBS、SIS和SIBS存在分子质量大、熔融指数低、熔体流动性差、透明性低、不易一次性注塑成型商用橡胶制品的缺陷,本发明的第一个目的是在于提供一种分子质量均衡、熔融指数大、高充油、高模量、低变形、拉伸强度大、熔体流动性高、制品高度透明,且易一次注塑成型为商品的复合型聚苯乙烯-共轭二烯多嵌段弹性体(下文简称SD-TPE),其综合物理性能优于现有的苯乙烯类热塑性弹性体(SDC)

Benefits of technology

[0035]针对现有的三嵌段结构和偶合型的SBS、SIS和SIBS存在分子质量大、熔融指数低、熔体流动性差,透明性低、不易一次性注塑成型商用制品的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117186326B_ABST
    Figure CN117186326B_ABST
Patent Text Reader

Abstract

The application discloses a styrene-conjugated diene-styrene triblock copolymer and a coupling compound elastomer thereof, and a preparation method and application thereof. The compound elastomer (SD-TPE) mainly comprises S-D-S and (S-D-S) n -Y m The SD-TPE has balanced molecular mass, large melt index, easy oil filling, high cohesion, low deformation, large tensile strength, high melt flowability, high transparency of products, and can be one-time injection molded into products, and the comprehensive physical properties are superior to those of existing styrene-diene copolymer thermoplastic elastomers (SDC). According to different formulas, the SD-TPE can be used as main materials of whole shoes, fine toys, rubber bands and rubber balls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a block conjugated diene-styrene elastomer, particularly to a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer, and also to its preparation method and application as a base rubber for toys, rubber bands, and shoe materials, belonging to the field of styrene thermoplastic elastomer (TPE) preparation technology. Background Technology

[0002] Existing anionic polymerization methods are used to prepare polystyrene-butadiene-styrene triblock copolymers, such as commercially available products produced by the Synthetic Rubber Plant of Sinopec Baling Petrochemical Company, including YH-791, YH-792, YH-791H, YH-805, YH-803, YH-1209, and YH-815, which are commonly known as SBS and SIS (commonly known as SDC). Linear SDC is typically prepared by a three-stage polymerization method, with a melt flow index (MFR) of 0.01–10 g / 10 min and a number-average molecular weight of 80,000–180,000. It is mainly used as modified asphalt for roads, asphalt waterproofing materials, shoemaking, and adhesives. Coupled SBS is prepared by two-stage polymerization followed by coupling with silicon tetrachloride. Its average number of coupling arms is between 2.5 and 3.5. The polymer has a larger molecular weight, with a number-average molecular weight Mn of 200,000–350,000. Its MFR is undetectable. Usually, a certain amount of white oil is added to the synthesized adhesive to make it an oil-extended adhesive, which makes it processable and usable.

[0003] There are numerous reports in the prior art regarding styrene-butadiene block copolymers and their production methods. For example, the technology disclosed in Chinese Patent (CN85102259A) aims to reduce the permanent deformation of the copolymer by using SBS or (SB) as the product. n The styrene to butadiene ratio (S / B) of R is ≥30 / 70, meaning the weight percentage of the S segment is greater than 30%. Although some technologies, such as Chinese patent (CN1088591A), disclose the preparation (SD)... nThe method for producing S (n = 2-4) products has an S segment weight percentage of 20%-45% and a D (butadiene-containing conjugated diene) segment weight percentage of 55%-80%. However, the product is a multi-block copolymer, and the initiator used in the synthesis process is a bislithium initiator, which is different from the initiator used in this invention. The SBS products produced by the above technology have higher S segment weight percentages and stronger resin properties. Chinese Patent (CN20913887A) discloses a method and process for preparing a styrene-butadiene-styrene block copolymer, describing a heated and pressurized polymerization reaction in a cyclohexane solution using butadiene, n-butyllithium, styrene, sodium dodecylbenzenesulfonate, and a composite structure modifier of pentamethyldiethyltriammonium, along with antimony trichloride as a coupling agent, to obtain a styrene-butadiene-styrene block copolymer with a styrene block content of 74%. Chinese Patent (CN102887980B) discloses a styrene-butadiene copolymer, its preparation method, and its application. This copolymer has a styrene-butadiene-styrene triblock structure, with the middle block primarily composed of random copolymerization of butadiene and styrene, combined with a styrene-butadiene-styrene block structure. The copolymer has a number-average molecular weight of 120,000–170,000, a molecular weight distribution of 1.01–1.1, a styrene mass fraction of 35–50%, and a butadiene mass fraction of 50–65%. Chinese Patent (CN 1073950A) discloses a method for preparing a styrene-butadiene block copolymer. The steps involve forming non-elastomeric blocks, generating randomized blocks, and finally forming elastomer-structure-modifying blocks in an organolithium-initiated styrene-butadiene anionic polymerization reaction. Finally, the resulting polymer chain containing active-terminated lithium groups is coupled with an alkoxysilane compound to generate a star-shaped styrene-butadiene random block copolymer. Chinese patent (CN9611838A) discloses a styrene-butadiene block copolymer and its manufacturing method. Cyclohexane is used as a solvent, n-butyllithium (BuLi) is used as an initiator, and tetrahydrofuran (THF) is used as an activator. The weight percentages of monomers styrene (S) and butadiene (B) are 10%–29% and 71%–90%, respectively. The concentration of the raw material monomers in the solvent is 12g–20g / 100ml. Linear SBS with a number average molecular weight Mn of 10±20,000 and (SB)nR (n is 3–4) with a number average molecular weight Mn of 18±20,000 are synthesized by three-step feeding segmental polymerization and two-step feeding coupling method, respectively.

[0004] In addition, a novel SBS waterproof coating with strong water resistance, high adhesion, good thermal stability, and environmental friendliness was disclosed in the literature ("Preparation of a Novel Styrene-Butadiene-Styrene Waterproof Coating", Electroplating and Finishing, No. 29(8)). Its composition includes SBS, terpene resin, ethyl acetate, toluene, etc. In the literature ("Research on Styrene-Butadiene-Styrene (SBS) Triblock Copolymer Building Adhesive", *China Adhesives*, 2007), a building adhesive was prepared using styrene-butadiene-styrene copolymer (YH-791 / YH-792), tackifying resin, antioxidant, and flame retardant. The initial tack and peel strength of the building adhesive were investigated under the sample conditions of m(YH-791):m(YH-792) = 7:3 or 6:4. # Gasoline combined with ethyl acetate can be used as an excellent solvent for building adhesives, and it has the highest oil resistance to engine oil.

[0005] In the paper "Molecular Structure Design and Hydrogenation of Star-Branched Butadiene Polymers," published by Dalian University of Technology, Chemical Engineering, 2021, star-branched polymers were introduced for their wide application due to their unique structure and properties. The synthesis of butadiene polymers based on star-branched structures is of significant research importance. Using living anionic polymerization and coupling modification techniques, bifunctional ether Lewis bases were selected as regulators, and divinylbenzene (DVB) as coupling agents. Two star-branched butadiene polymers were successfully designed and synthesized: high-1,2-structure star-branched polybutadiene (Sg-PB) and a star-branched styrene-butadiene-styrene copolymer with polystyrene as the regular branch. Subsequently, hydrogenation was performed using unsaturated double bonds to generate the corresponding hydrogenation products: star-branched hydrogenated polybutadiene (SgH-PB) and star-branched SEBS (Sg-SEBS).

[0006] In summary, the synthesis of SBS generally involves a three-step addition method in an inert solvent, using a monofunctional organolithium compound as an initiator: first, styrene is added for polymerization, then butadiene is added for further polymerization, and finally, styrene is added again for polymerization. The reaction is terminated with a terminator to obtain a linear block copolymer, SBS. Alternatively, a two-step addition method followed by coupling with a coupling agent is used: first, styrene is added for polymerization, then butadiene is added for further polymerization. After the reaction is complete, a coupling reaction is performed with a coupling agent to obtain a star-shaped block copolymer, SBS. As professionals know, changing the order or method of adding styrene S and butadiene B (e.g., mixing styrene S and butadiene B) can yield a series of new styrene-butadiene multi-block polymers, which are the well-known commercially available SBS or thermoplastic elastomers (TPEs). These elastomers are commonly used as modified asphalt, solvent-based adhesives, and shoe sole materials. However, existing SBS molecules have a large molecular weight, low melt index, and poor polymer flowability, making it impossible to produce transparent shoes where the entire main material, such as the sole, upper, and upper, is made of SBS and molded in one piece; it also cannot be used to make transparent products such as delicate toys and rubber bands.

[0007] There are currently no corresponding technologies or reports on styrene-based elastomers that possess good melt flowability, easy injection molding, high transparency, high strength, and adjustable hardness. Summary of the Invention

[0008] To address the shortcomings of existing triblock structures and coupled SBS, SIS, and SIBS, which suffer from high molecular weight, low melt index, poor melt flowability, low transparency, and difficulty in one-time injection molding into commercial rubber products, the first objective of this invention is to provide a composite polystyrene-conjugated diene multiblock elastomer (hereinafter referred to as SD-TPE) with balanced molecular weight, high melt index, high oil filling, high modulus, low deformation, high tensile strength, high melt flowability, high product transparency, and easy one-time injection molding into commercial products. Its comprehensive physical properties are superior to existing styrene-based thermoplastic elastomers (SDC).

[0009] Another object of the present invention is to provide a simple, low-cost, and mild method for preparing the SD-TPE.

[0010] The third objective of this invention is to provide an application of SD-TPE, which can be used in injection-molded rubber products, such as toys, elastic bands, and elastic rubber products with integrated sole-upper or sole-upper-shoe upper. The prepared rubber products have high transparency and comprehensive physical properties superior to existing styrene-diene copolymer thermoplastic elastomers (SDC).

[0011] To achieve the above-mentioned technical objectives, the present invention provides a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer, which comprises SDS and (SDS). n -Y m SDS is a styrene-conjugated diene-styrene triblock copolymer. n -Y m It is a styrene-conjugated diene-styrene triblock copolymer coupling; Y is the coupling junction, n is the number of coupling arms, m is the number of coupling junctions, S is the styrene homopolymer block, and D is the polyconjugated diene block.

[0012] As a preferred solution, m and n are both positive integers, and n>m, 2≤n≤5, m≥1.

[0013] As a preferred embodiment, the SDS or (SDS) n -Y m The block mass ratio of styrene units to conjugated diene units is (35-45) / (65-55). More preferably, the block mass ratio of styrene units to conjugated diene units is (38-43) / (62-57). If the styrene block mass is too low, the polymer has low hardness and high elongation; if the styrene block mass is too high, the polymer has low elongation, high strength, and high modulus. Therefore, it is necessary to control the ratio within the preferred range.

[0014] As a preferred embodiment, D is a butadiene homopolymer block, an isoprene homopolymer block, or a butadiene and isoprene copolymer block. More preferably, the butadiene and isoprene copolymer block can be a random copolymer block of the two or a diblock structure.

[0015] As a preferred embodiment, the mass percentage of the 1,2-structural units of the butadiene unit and / or the 3,4-structural units of the isoprene unit in D is 10-30%. In the SD-TPE of this invention, the side-branched groups do not need to be excessive; controlling them within a conventional range is sufficient to achieve the desired physical properties. Excessive amounts of 1,2-structural butadiene units and 3,4-structural isoprene units require additional structure modifiers during the polymerization reaction, increasing manufacturing costs.

[0016] As a preferred embodiment, the number-average molecular weight of the SDS is Mn = 4.5 × 10⁻⁶. 4 ~8.0×10 4 .

[0017] As a preferred embodiment, the (SDS) n -Y m The number-average molecular weight Mn = 9.0–17.0 × 10⁻⁶ 4.

[0018] As a preferred embodiment, the molecular weight ratio (MFR) of the styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer is 5–15 g / 10 min, and the MFR is tested according to GB / T 3682.1 standard. It is worth noting that the lower molecular weight SDS in the composite elastomer is beneficial for the elastomer to have good extrusion and injection molding processability and the transparency of the finished product; while the higher molecular weight (SDS)... n -Y m This molecular structure and composition, which helps to ensure the strength and usability of composite materials, integrates the processing and performance properties of composite materials.

[0019] As a preferred embodiment, Y is a coupling residue of at least one of dichlorodimethylsilane, dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, and silicon tetrachloride, or a divinylbenzene addition unit. Residues formed by coupling dichlorodimethylsilane, dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, and silicon tetrachloride with terminal active lithium of SDS can also be monomeric or dimeric DVB core units formed by the addition of divinylbenzene (DVB) to terminal active lithium of SDS.

[0020] As a preferred embodiment, the SDS and (SDS) n -Y m The mass percentage composition is 85-95% : 5-15%. It is worth further noting that the lower molecular weight and higher concentration of SDS in the SD-TPE component gives the elastomer good melt flowability (easy injection molding) and transparency; the higher molecular weight and lower concentration of SDS... n -Y m This ensures the elastomer has high strength and avoids an increase in haze in SD-TPE products. The higher polystyrene block content in SD-TPE is beneficial for the elastomer's high strength and facilitates the filling of more softening rubber oil, reducing product costs, while ensuring sufficient elasticity and suitable hardness in the product. Therefore, controlling SDS and (SDS) is crucial. n -Y m Maintaining the appropriate ratio is crucial for the performance of SD-TPE elastomers.

[0021] This invention also provides a method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer. The preparation method involves adding a portion of styrene monomer to an anionic polymerization system for a first-stage polymerization, then adding a conjugated diene monomer for a second-stage polymerization, and then adding the remaining portion of styrene monomer for a third-stage polymerization. After the polymerization is completed, a coupling agent is added to carry out a coupling reaction. After the coupling reaction is completed, the reaction is terminated, and the resulting adhesive solution is successively coagulated and dried to obtain the final product.

[0022] As a preferred embodiment, the anionic polymerization system includes an activator, an initiator, and a solvent.

[0023] As a preferred embodiment, the activator is tetrahydrofuran. As a further preferred embodiment, the amount of activator used is 20-30 mg / kg solvent. A lower amount of activator can adjust the proportion of 1,2-addition of butadiene monomer and 3,4-addition of isoprene monomer to be in the range of 10-30%.

[0024] As a preferred embodiment, the initiator is n-butyllithium. The amount of initiator used is conventional and determined based on the molecular weight of the polymer.

[0025] As a preferred embodiment, the solvent is cyclohexane and / or hexane.

[0026] As a preferred embodiment, the conditions for the first polymerization stage are: temperature of 50-60℃ and time of 20-30 min.

[0027] As a preferred embodiment, the conditions for the second polymerization stage are: temperature of 65–90°C and time of 20–30 min.

[0028] As a preferred embodiment, the conditions for the third polymerization stage are: a temperature of 50–80°C and a time of 20–30 min.

[0029] As a preferred embodiment, the coupling reaction conditions are: a temperature of 50–80°C and a time of 20–30 min.

[0030] As a preferred embodiment, the coupling agent is at least one selected from dichlorodimethylsilane, dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, and silicon tetrachloride. As a more preferred embodiment, the amount of coupling agent added is 2.5% to 8% of the molar amount of the active polymer molecules in the polymerization system. By controlling the amount of coupling agent added, the desired balance of SDS and (SDS) in SD-TPE can be achieved. n -Y m Effective regulation of the ratio between the two.

[0031] As a preferred embodiment, the termination reaction uses a haloalkane or halosilane as a terminating agent, which can react with active lithium (SBS). - Li + This forms a neutral salt, specifically C2-C8 haloalkanes and trimethylchlorosilane, etc. More preferably, bromoethane, bromoisopropane, bromobutane, chlorobutane, and trimethylchlorosilane are used in amounts equivalent to the active lithium, converting the active lithium into neutral lithium halides. The purpose is to prevent the active lithium polymer from coupling with oxygen in the air after discharge to form large molecules, and also to prevent the antioxidant from reacting with the alkaline lithium in the adhesive solution, causing discoloration and affecting the transparency of the finished adhesive.

[0032] This invention also provides an application of styrene-conjugated diene-styrene triblock copolymers and their coupling composite elastomers in rubber products, particularly in injection-molded rubber products. Specifically, this includes toys, elastic bands, and elastic rubber products with integrated sole-upper or sole-upper-vein construction.

[0033] As a preferred embodiment, the rubber product comprises the following components in parts by weight: 75 parts of a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer; 20-40 parts of filler oil; and 0.15-0.20 parts of brightener. The preferred filler oil is a naphthenic white oil, and the preferred brightener is OB-1 fluorescent brightener.

[0034] Compared with existing technologies, the beneficial effects of the technical solution of this invention are as follows:

[0035] Existing triblock and coupled SBS, SIS and SIBS have drawbacks such as large molecular weight, low melt index, poor melt flowability, low transparency, and difficulty in one-time injection molding of commercial products.

[0036] The SD-TPE provided by this invention has a balanced molecular weight, a high melt index, good melt flowability, high oil filling capacity without sacrificing cohesion and elastic modulus, low deformation, and highly transparent products. Furthermore, the designed products can be easily injection molded in one step. Its comprehensive physical properties are superior to existing pure low molecular weight SBCs (YH-788 and SIS-1105) and higher molecular weight SBCs (such as YH-791, YH-703, YH-803 and SIS-1126).

[0037] The SD-TPE hot melt adhesive sheet of the present invention has the following properties: 300% tensile stress ≥7.0MPa, tensile strength ≥30MPa, Shore A hardness 85-95, light transmittance >88%, and MFR of 5-15g / 10min.

[0038] The SD-TPE preparation method of the present invention is simple, low-cost, and mild, which is conducive to large-scale production. Attached Figure Description

[0039] Figure 1 H is the SBS-2# prepared in Example 2. 1 -NMR spectrum.

[0040] Figure 2 A comparison of the transparency of TPE988 and SBS3546 hot melt adhesive sheets.

[0041] Figure 3 Dynamic viscoelastic spectrum (DMA) analysis of TPE988 and SBS3546 hot melt adhesive sheets; from Figure 3 DMA test results show that, within the temperature range of 30℃ to 50℃, compared with SBS3546 with the same oil filling, TPE988 has a lower loss factor (tanδ) and dynamic heat generation, and a higher elastic modulus (E') than SBS3546. After oil filling, TPE988 has better dynamic deformation resistance. Detailed Implementation

[0042] The present invention is illustrated by the following embodiments, which do not constitute a limitation on the scope or implementation of the present invention.

[0043] In the following examples, the number-average molecular weight and molecular weight distribution of polymers were determined using a Shimadzu LC-20AD liquid gel permeation chromatograph (GPC). The mobile phase was THF with a concentration of 1 mg / ml, the flow rate was 1.0 ml / min, the injection volume was 20 μl, and gel chromatography columns 804 and 805 were used in series. PS was used as a standard.

[0044] The microstructure of the polymer was analyzed using a Swiss Bruker AVANCE NEO-400 nuclear magnetic resonance spectrometer, with CDCl3 as solvent and TMS as internal standard, at room temperature, according to GB / T 28728.

[0045] The haze of the fused-on film was tested using a Shanghai Jingke WGT-2S transmittance and haze meter.

[0046] According to GB / T 528 Test of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber; according to GB / T 531.1 Test method for indentation hardness - Part 1: Shore hardness test; according to GB / T 3682.1 Determination of melt mass flow rate (MFR) of thermoplastic plastics - Part 1: Standard method.

[0047] The dynamic heat generation of the compressed adhesive was tested using a DMA3300 dynamic mechanical analyzer from Thermomix (TAI). The test conditions were: frequency 5 Hz, amplitude 0.5%, and heating rate 3 °C / min.

[0048] Example 1

[0049] Under nitrogen protection, add 3000 mL of cyclohexane solution containing 0.10 mL of activator THF and 70 mL of styrene to a 5 L polymerization reactor. Start stirring and heat the material to 55 °C. Then add 0.5 mol / L n-butyllithium NBL14.5. The polymerization process was initiated and carried out for 25 minutes with mL of styrene (including the active lithium consumed by the dehumidification steam). Next, 318 mL of butadiene was added to the polymerization reactor at 80 °C and stirred for 25 minutes. Then, 70 mL of styrene was added to the polymerization reactor and polymerized at 75 °C for 25 minutes. Then, 3.5 mL of a 0.10 mol / L dichlorodimethylsilane cyclohexane solution was added to the polymer solution in the polymerization reactor and coupled at 68 °C for 25 minutes. Finally, 12.4 mL of a 0.5 mol / L bromoethane cyclohexane solution was added to the polymerization reactor and stirred at 55 °C for 20 minutes to terminate the polymerization, resulting in a colorless and transparent polymer solution. After adding 0.80 g of antioxidant 1076 to the colorless and transparent polymer solution and stirring evenly, the polymer solution was condensed and dried with water vapor to obtain colorless polymer particles (labeled as SBS-1#).

[0050] Results: The GPC analysis of the obtained colorless and transparent dry adhesive SBS-1# is shown in Table 1.

[0051] Example 2

[0052] The relevant process conditions in Example 1 were kept unchanged, except that 14.0 mL of NBL was used, 72 mL of styrene was added in the first and third stages, 310 mL of butadiene was added in the second stage, and 3.2 mL of dichlorodimethylsilane cyclohexane solution was used for coupling.

[0053] Results: GPC analysis of the obtained colorless and transparent dry adhesive is shown in Table 1 for the SBS-2# label; H1-NMR spectrum is shown in Table 1. Figure 1 .

[0054] Example 3

[0055] The relevant process conditions in Example 2 were kept unchanged, except that 13.0 mL of NBL was used, 75 mL of styrene was added in the first and third stages, 305 mL of butadiene was added in the second stage, 3.1 mL of 0.10 mol / L divinylbenzene cyclohexane solution was used for coupling, and 8.5 mL of 0.5 mol / L trichlorosilane cyclohexane solution was used as the terminator.

[0056] Results: The GPC analysis of the obtained colorless and transparent dry adhesive is shown in Table 1, labeled SBS-3#.

[0057] Example 4

[0058] The relevant process conditions in Example 2 were kept unchanged, except that 13.5 mL of NBL was used and 2.8 mL of a cyclohexane solution of 0.1 mol / L trichloromethylsilane was selected as the coupling agent.

[0059] Results: The GPC analysis of the obtained colorless and transparent dry adhesive is shown in Table 1, labeled SBS-4#.

[0060] Example 5

[0061] The relevant process conditions in Example 4 were kept unchanged, except that 12.0 mL of NBL was used and 2.3 mL of a 0.1 mol / L silicon tetrachloride cyclohexane solution was selected as the coupling agent.

[0062] Results: The GPC analysis of the obtained colorless and transparent dry adhesive is shown in Table 1, labeled SBS-5#.

[0063] Example 6

[0064] The relevant process conditions in Example 4 were kept unchanged, except that 11.0 mL of NBL was used, and the coupling agent was selected as 1.8 mL of 0.1 mol / L silicon tetrachloride cyclohexane solution and 1.5 mL of 0.10 mol / L dichlorodimethylsilane cyclohexane solution.

[0065] Results: The colorless and transparent dry adhesive GPC analysis results are shown in Table 1 for SBS-6#.

[0066] Example 7

[0067] The relevant process conditions in Example 2 were kept unchanged, except that 12.0 mL of NBL was used, 68 mL of styrene was added in the first and third stages, 218 mL of butadiene and 100 mL of isoprene were added in the second stage, 3.3 mL of dichlorodimethylsilane cyclohexane solution was used for coupling, and 9.0 mL of 0.5 mol / L bromoisopropane cyclohexane solution was used as the terminator.

[0068] Results: The colorless and transparent dry adhesive GPC analysis results are shown in Table 1, labeled SIBS-7#.

[0069] Example 8

[0070] The relevant process conditions in Example 1 were kept unchanged, except that 14.0 mL of NBL was used, 76 mL of styrene was added in the first and third stages, 120 mL of butadiene and 200 mL of isoprene were added in the second stage, and 5.5 mL of 0.1 mol / L divinylbenzene cyclohexane solution was used for coupling.

[0071] Results: The colorless and transparent dry adhesive GPC analysis results are shown in Table 1, labeled SIBS-8#.

[0072] Example 9

[0073] The relevant process conditions in Example 8 were kept unchanged, except that 10.5 mL of NBL was added, 290 mL of isodiene was added in the second stage, and 3.0 mL of a cyclohexane solution of 0.1 mol / L dimethyldiethoxysilane was used for coupling.

[0074] Results: The colorless and transparent dry adhesive GPC analysis results are shown in Table 1, labeled SIBS-9#.

[0075] Comparative Example 1

[0076] The relevant process conditions in Example 1 were kept unchanged, except that 76 mL of styrene was added in both the first and third stages of NBL 12.0 mL, and the coupling amount was 4.0 mL.

[0077] Results: The final adhesive solution exhibited a bluish tint, and the number-average molecular weight (Mn) of SBS in the polymer was 6.75 × 10⁻⁶. 4 The mass fraction was 80.21%; the number-average molecular weight Mn of (SBS)₂-Si was 13.97 × 10⁻⁶. 4 The mass fraction was 18.47%, and the resulting dry glue was cloudy with an MFR of 0.24 g / 10 min. This polymer is not easy to inject mold.

[0078] Comparative Example 2

[0079] The relevant process conditions in Example 3 were kept unchanged, except that 75 mL of styrene was added in the first and third stages of NBL 10.5 mL, 305 mL of butadiene was added in the second stage, and 5.0 mL of 0.10 mol / L divinylbenzene (Y) cyclohexane solution was used for coupling.

[0080] Results: The adhesive solution after termination exhibited a bluish tint, and the Mn content of SBS in the polymer was 8.87 × 10⁻⁶. 4 The mass fraction was 77.64%; (SBS) n -Y m The Mn content is 19.78 × 10⁻⁶. 4 The mass fraction was 19.83%, and the resulting dry glue was cloudy with an MFR of 0.06 g / 10 min. This polymer is not easy to inject mold.

[0081] Comparative Example 3

[0082] The relevant process conditions in Example 1 were kept unchanged, except that 13.5 mL of NBL was used, 72 mL of styrene was added in the first and third stages, 310 mL of butadiene was added in the second stage, and 2.4 mL of dichlorodimethylsilane cyclohexane solution was used for coupling.

[0083] Results: The number-average molecular weight (Mn) of SBS in the terminated polymer was 5.48 × 10⁻⁶. 4 The mass fraction was 93.54%; the number-average molecular weight Mn of (SBS)₂-Si was 11.42 × 10⁻⁶. 4 The mass fraction was 4.72%. The resulting dry glue melt sheet had a light transmittance of 87.53% and an MFR of 17.45 g / 10 min (which is relatively high).

[0084] Table 1 shows the molecular weight and distribution of the polymer (SD-TPE) in the examples.

[0085]

[0086]

[0087] Note: The contents of 3,4-unit and vinyl unit are the mass fractions in the isoprene segment and polybutadiene segment, respectively.

[0088] Example 10

[0089] The SBS-1#, SBS-2#, SBS-3#, SBS-4#, SBS-5#, SBS-6#, SIBS-7#, SIBS-8#, SIS-9# prepared in Examples 1 to 9, as well as commercially available TPE-988, SBS 3546, SIS-1209, SBS-788, and Comparative Example 1 and Comparative Example 3 dry adhesives were hot-melt pressed into sheets, and their physical properties are shown in Table 2.

[0090] Table 2 Physical properties of dry adhesives 5-17

[0091]

[0092]

[0093] Note: TPE-988 is an industrial product prepared based on the process conditions in Example 2; SBS 3546 is traded as LCY3546, with an S / B ratio of 4 / 6; SIS-1209 has an S / I ratio of 3 / 7; and SBS-788 has an S / B ratio of 3 / 7.

[0094] As can be seen from Table 2, the physical properties of existing SBS and SIS are inferior to those of the polymer (SD-TPE) of this invention.

[0095] Example 11

[0096] The 75 parts of dry adhesives from Examples 10 (SBS-2#, SBS-3#, SBS-5#, SIBS-7#, SIBS-8#, SIS-9#, TPE-988, SBS3546, SIS-1209, YH-803 and Comparative Examples 1 and 3) were respectively filled with 25 parts of KN4010 white oil and 17 parts of OB-10 and blended. The physical properties of the hot melt pressed sheets are shown in Table 3.

[0097] Table 3 Physical properties of oil-extended rubber

[0098]

[0099]

[0100] Note: MFR test conditions are 190℃ / 2.16Kg; YH-803 is a star-shaped product, S / B=4 / 6, Mn=30×10 4 .

[0101] As shown in Table 3, compared to the polymer of this invention, the comparative example exhibits a low molecular weight filtration (MFR), indicating poor injection molding performance; conversely, the comparative example has a high MFR, resulting in excessive polymer melt flowability, leading to large shrinkage and deformation, low strength, and unusability of the molded product. The SD-TPE of this invention has significantly superior overall physical properties compared to existing commercially available products, with SIS-1209 and YH-803 used as the main materials for hot melt pressure-sensitive adhesives and shoe outsoles, respectively.

Claims

1. A styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer, characterized in that: Includes SDS and (SDS) n -Y m ; in, SDS is a styrene-conjugated diene-styrene triblock copolymer; (SDS) n -Y m It is a styrene-conjugated diene-styrene triblock copolymer coupling; Y represents the coupling junction, n represents the number of coupling arms, m represents the number of coupling junctions, S represents the styrene homopolymer block, and D represents the polyconjugated diene block. The SDS or (SDS) n -Y m The block mass ratio of styrene units to conjugated diene units is (35–45) / (65–55); the number-average molecular weight Mn of the SDS is 4.5 × 10⁻⁶. 4 ~8.0×10 4 The (SDS) n -Y m The number-average molecular weight Mn = 9.0 × 10 4 ~17.0×10 4 The SDS and (SDS) n -Y m The mass percentage composition is: 85-95% : 5-15%; Both m and n are positive integers, and n>m, 2≤n≤5, m≥1; The Y is a coupling residue of at least one of dichlorodimethylsilane, dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, and silicon tetrachloride, or a divinylbenzene addition unit.

2. The styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 1, characterized in that: D is a butadiene homopolymer block, an isoprene homopolymer block, or a butadiene and isoprene copolymer block.

3. The styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 2, characterized in that: The mass percentage of the 1,2-structural units of the butadiene unit and / or the 3,4-structural units of the isoprene unit in D is 10-30%.

4. The styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 1, characterized in that: The MFR of the styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer is 5-15 g / 10 min.

5. A method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to any one of claims 1 to 4, characterized in that: In anionic polymerization system, a portion of styrene monomer is first added for the first stage of polymerization, then a conjugated diene monomer is added for the second stage of polymerization, and then the remaining portion of styrene monomer is added for the third stage of polymerization. After polymerization is completed, a coupling agent is added for coupling reaction. After coupling reaction is completed, the reaction is terminated, and the resulting adhesive is then coagulated and dried sequentially to obtain the final product.

6. The method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 5, characterized in that: The anionic polymerization system contains an activator, an initiator, and a solvent.

7. The method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 6, characterized in that: The activator is tetrahydrofuran; The activator is used at a dosage of 20-30 mg / kg solvent; The initiator is n-butyllithium; The solvent is cyclohexane and / or hexane.

8. The method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 6, characterized in that: The conditions for the first polymerization stage are: temperature 50-60℃, time 20-30 min; The conditions for the second stage of polymerization are: temperature 65–90℃, time 20–30 min; The conditions for the third stage polymerization are: temperature 50-80℃, time 20-30min; The conditions for the coupling reaction are: temperature of 50–80°C and time of 20–30 min.

9. The method for preparing a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 6, characterized in that: The coupling agent is at least one of dichlorodimethylsilane, dimethyldimethoxysilane, methyltrimethoxysilane, tetramethoxysilane, and silicon tetrachloride; the amount of the coupling agent added is 2.5% to 8% of the molar amount of the active polymer molecules in the polymerization system.

10. The application of the styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to any one of claims 1 to 4, characterized in that: Used in rubber products.

11. The application of the styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 10, characterized in that: Rubber products used in injection molding.

12. The application of a styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer according to claim 10 or 11, characterized in that: The rubber product comprises the following components in parts by weight: 75 parts of styrene-conjugated diene-styrene triblock copolymer and its coupling composite elastomer; 20-40 parts of filler oil; and 0.15-0.20 parts of whitening agent.

Citation Information

Patent Citations

  • Styrene-butadiene copolymer as well as preparation method and application thereof

    CN102887980B

  • Preparation method of styrene-butadiene block copolymer

    CN1073950A

  • Multi-inlay section thermal plastic elastic body and synthesis method

    CN1088591A

  • Prepn. of block polymers

    CN85102259A

  • Asymmetric star type styrene-butadiene rubber, and preparation method thereof and applications of asymmetric star type styrene-butadiene rubber as sole rubber material

    CN107501488A